2018
DOI: 10.3390/socsci7100183
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Economic Growth in Mexico

Abstract: The relationship between poverty and economic growth has been widely discussed in the economic development literature during the past few decades. However, most of this research has been based on cross-sectional studies and very few studies have used time-series techniques to analyze this important issue. At the same time, there are also only a few studies analyzing this issue for the case of Mexico. Therefore, the objective of this paper was to analyze the relationship between poverty and economic growth in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 24 publications
5
39
0
2
Order By: Relevance
“…Some studies, such as that of Jiménez Pozo et al (2006) for the case of Bolivia do not find evidence that female headship of the family increases poverty, as did (Székely 1998) for the case of Mexico. For this same country Garza-Rodríguez (2015), Serratos (2015) and Fernández-Ramos et al (2016) find evidence that households headed by women are more likely to be poor.…”
Section: Empirical Evidencementioning
confidence: 98%
See 2 more Smart Citations
“…Some studies, such as that of Jiménez Pozo et al (2006) for the case of Bolivia do not find evidence that female headship of the family increases poverty, as did (Székely 1998) for the case of Mexico. For this same country Garza-Rodríguez (2015), Serratos (2015) and Fernández-Ramos et al (2016) find evidence that households headed by women are more likely to be poor.…”
Section: Empirical Evidencementioning
confidence: 98%
“…Gender of Household Head Many studies have analyzed whether the gender of the head of the family is related to poverty, particularly if the fact that the head of the family is female increases the probability that the household is poor. This phenomenon, known as the feminization of poverty (Pearce 1978), can be explained by discrimination against women in the labor market but also because women tend to have less education than men, which is why they receive less income in the labor market (Garza-Rodríguez 2015). Most studies have found evidence in favor of the feminization of poverty (Biyase and Zwane 2018;Chen and Wang 2015;Iqbal et al 2020;Ravindra Deyshappriya and Minuwanthi 2020;Teka et al 2019).…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Dalam kaitannya dengan pertumbuhan ekonomi, secara literatur, kemiskinan merupakan salah satu faktor yang dapat mempengaruhi pertumbuhan ekonomi. Para ekonom setuju bahwa kemiskinan dan pertumbuhan ekonomi memiliki hubungan terbalik atau negatif (Alvaredo & Gasparini, 2015;Garza-Rodriguez, 2018;Karim et al, 2013;Škare & Družeta, 2016). Studi lain juga menyatakan bahwa perlambatan pertumbuhan ekonomi telah menyebabkan adanya kemiskinan (Aba et al, 2015).…”
Section: Kajian Pustaka Dan Perumusan Hipotesisunclassified
“…Meanwhile, Nyasha, Gwenhure & Odhiambo (2017) and Nuruddeen & Ibrahim (2014) have found a unidirectional causality running from poverty reduction to economic growth. Other studies have revealed that the nexus between poverty and economic growth has a long-run bidirectional causality (Afzal et.al, 2012;Garza-Rodriguez, 2018 ;Dewi et al, 2018) while in the case of Nigeria, Okoroafor and Chinweoke (2013); Nindi & Odhiambo (2015) have argued that there is no relationship between economic growth and poverty.…”
Section: Introductionmentioning
confidence: 99%